MEDIA ELECTRONIC FLASHCARD KEANEKARAGAMAN JENIS TUMBUHAN MANGROVE DI HUTAN LINDUNG TANJUNG PRAPAT MUDA - Handayani, Dea Fitri; Daningsih, Entin; Mardiyyaningsih, Asriah Nurdini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Mangrove forests experience degradation every year. One of the effort to protect and preserve mangroves is to increase knowledge through disseminating information about mangroves. Knowledge about mangrove can be included in the learning process through media at school, so that students can understand the important role of mangroves in life. The aim was of this research is were to create and validate an electronic flashcard (e-flashcard) media for the diversity of mangrove plant species. The research method used descriptivequantitative. E-Flashcards are made in three stages, namely preproduction, production, and post-production. The E-Flashcard validation stage consisted of validating the instrument validation questionnaire sheet and the media validation. The items assessed on the media validation sheet consisted of 5 aspects (format, content, language, effectiveness, and practicality) with 14 criteria assessed using a Likert scale. Validation was carried out by 5 validators consisting of 2 biology education lecturers at FKIP Tanjungpura University and 3 Senior High School at class X biology teachers. The results showed that the average CVI value attanined 1.00 was declared valid. In conclucion e"“flashcard of plant diversity of mangrove species can be used as a learning medium in the diversity sub-material of Senior High School at class X.